2012
DOI: 10.1115/1.4005186
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Mechanical and Laser Cutting on the Fatigue Strengths of Square Hollow-Section Welded T-Joints

Abstract: T-joint connections are commonly encountered in many machine components and load carrying members. The T-joint connections can be fabricated using traditional cutting (machine or flame) or by laser cutting techniques. The present study investigates the feasibility of using laser cutting to produce welded square hollow-section T-joints with similar or higher fatigue strengths than their conventional mechanical cut counterparts. A total of 21 full-scale T-joint samples, typical of those found in the agricultural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Furthermore, practical difficulties regarding the mechanical cutting process, fabrication as well as control of the tolerance also seems to remain an open question[28]*. This study therefore aims at solving this practical limitation in the implementation of "passing-through" design solutions by using the Laser Cutting Technology (LCT), which offers several advantages compared to the conventional mechanical cutting procedure like increasing the fatigue strength[29], reducing the welding quantities, minimizing human errors with computer-programmed automation and offering a swift fabrication process, hence providing an efficient framework to further investigate the "passing-through" connections[30]. The advantages offered by the LCT, the aforementioned potential of the "passing-through" connections and the possibility to design moment-resisting connections with through plates constitutes the bases of the present research study.In order to achieve a better moment resistance than the conventional open-to-CHS connections, several types of two-way and four-way rigid connections were investigated in the "LASTEICON" research project using the "passing-through" approach, funded by the European Commission[31].…”
mentioning
confidence: 99%
“…Furthermore, practical difficulties regarding the mechanical cutting process, fabrication as well as control of the tolerance also seems to remain an open question[28]*. This study therefore aims at solving this practical limitation in the implementation of "passing-through" design solutions by using the Laser Cutting Technology (LCT), which offers several advantages compared to the conventional mechanical cutting procedure like increasing the fatigue strength[29], reducing the welding quantities, minimizing human errors with computer-programmed automation and offering a swift fabrication process, hence providing an efficient framework to further investigate the "passing-through" connections[30]. The advantages offered by the LCT, the aforementioned potential of the "passing-through" connections and the possibility to design moment-resisting connections with through plates constitutes the bases of the present research study.In order to achieve a better moment resistance than the conventional open-to-CHS connections, several types of two-way and four-way rigid connections were investigated in the "LASTEICON" research project using the "passing-through" approach, funded by the European Commission[31].…”
mentioning
confidence: 99%
“…Kanyilmaz (2019) characterised the problematic nature of the production of steel hollow profile connections and indicated LCT as a remedy for the problems arising in this production. Moazed and Fotouhi (2012) investigated the possibility of using LCT for producing welded square hollow-section T-joints, and compared the fatigue strength between T-joints obtained by mechanical cutting and laser cutting. 21 full-scale experiments with cyclic loading showed that the fatigue strength of the laser-cut samples was higher compared to those obtained with mechanical cutting.…”
Section: Literature Reviewmentioning
confidence: 99%